Investigation on Optimum Plot Size for Forest Inventory in East Karimnagar Forests - Tiwari, K. P.; Parthasarathy, V. (Indian Forester, 1975)
Investigations on optimum plot size for tropical dry deciduous forests of East Karimnagar Division Andhra Pradesh was undertaken with three circular plot sixes of 0.05, 0.1 and 0.2 ha on 38 plots in each case. Basal area, volume and tree count were obtained for all the three plot sizes and the SE % were compared. It was found that 0.1 ha circular plot size is optimum from all considerations and is recommended for use in similar forest types for forest inventory purposes.